CO2 hydrogenation to formic acid over heterogenized ruthenium catalysts using a fixed bed reactor with separation units - Park, Kwangho; Gunasekar, Gunniya Hariyanandam; Kim, Seong-Hoon; Park, Hongjin; Kim, Samhwan; Park, Kiyoung; Jung, Kwang-Deog; Yoon, Sungho (ROYAL SOC CHEMISTRY, 2020)
Along with the mitigation of CO2 emission, recently, the CO2-derived formic acid process has drawn attention as a promising platform for the renewable-energy-derived hydrogen storage cycle by using formic acid as a liquid organic hydrogen carrier (LOHC). Here, a heterogenized Ru molecular catalyst on a bpyTN-30-CTF support is prepared and successfully implemented in an integrated trickle-bed reactor system for continuous CO2 hydrogenation to produce formic acid. The bpyTN-30-CTF support with an alternative structure of the bpy and TN motif increases the porosity and metal anchoring sites. The Ru/bpyTN-30-CTF catalyst prepared using the bpyTN-30-CTF support displays sufficient catalytic activity for commercialization. Under the continuous process, the catalyst exhibits substantial catalytic performance with the highest productivity of 669.0 g(form.) g(cat)(-1) d(-1) with CO2 conversion of 44.8% for a superficial gas velocity of 72 cm s(-1). Furthermore, the catalyst shows excellent stability in the continuous hydrogenation process with a trickle-bed reactor over 30 days of operation, reaching a total turnover number of 524 000 without any significant deactivation. Based on kinetic data, a new process to produce formic acid by CO2 hydrogenation has thus been proposed here.
Keywords: COVALENT TRIAZINE FRAMEWORKS; CARBON-DIOXIDE; CAPTURE; FORMATE; EQUILIBRIUM; CONVERSION; METHANOL